Sistema pigmentar extrategumentar de Biomphalaria glabrata (Say, 1818) infectada e não infectada pelo Schistosoma mansoni (Sambon, 1907) e as alterações histológicas ocorridas pós-infecção - Andrade, Natalia Morais de (2009)
Schistosomiasis is an endemic parasitic disease typical of the Americas, Asia and Africa consisting of a major public health problem. The maintenance of the life cycle of Schistosoma mansoni in their intermediate hosts depends, among other factors, the mechanisms of defense which is performed by hemocytes with reticular pigmentary cells and metals present in the hemolymph of the snail. In this study, we sought to describe the extracutaneous pigment system of B. glabrata infected and not infected with S. mansoni and histological changes occurring post-infection. 44 were infected snails were put out for histological analysis every ten days post-infection resulting in an analysis in 10, 20 and 30 days. After fixation procedures, the specimens were cut and stained by nine stains for histological observation under a light microscope and confocal. For control we used 50 specimens of non-infected snails. Two categories phones were found in both the control and the three groups of infected snails. One group was formed by small pigmented dendritic cells and appeared predominantly in muscle with no difference regarding the amount and size when compared to the control group and infected. The second category was formed by reticular pigment cells that showed a wide distribution throughout the body of the snail. This category was different both in quantity and size when compared to the control and infected groups. The developmental stages were observed in groups of 20 and 30 days of infection while the granulomatous reactions were found either in the three study periods after infection and control groups. The relationship between snail and parasite is essential for understanding the biology of the parasite in its intermediate hosts and the development of methods to control snails in endemic areas. Although many studies about the host-parasite relationship in S. mansoni, the appearance of pigment cells had not yet been reported in invertebrates, thus confirming the presence of these cells becomes important in the elucidation of their role in host-parasite relationship.